2020
DOI: 10.1155/2020/1208726
|View full text |Cite
|
Sign up to set email alerts
|

Amelioration by Idesia polycarpa Maxim. var. vestita Diels. of Oleic Acid-Induced Nonalcoholic Fatty Liver in HepG2 Cells through Antioxidant and Modulation of Lipid Metabolism

Abstract: Idesia polycarpa Maxim. var. vestita Diels (I. polycarpa) is well known as an edible oil plant which contains abundant linoleic acid and polyphenols. The objective of this study was to maximize the by-product of defatted fruit of I. polycarpa. We found that the fraction D of ethyl acetate extract (EF-D) contained more polyphenols, which contribute to its strong antioxidant activity by antioxidant assays (DPPH, ABTS, and FRAP). Meanwhile, EF-D showed a significant lipid-lowering effect on oleic acid- (OA-) indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…When the activity of CYP7A1 decreases, the conversion of cholesterol to bile acid is blocked, resulting in an increased level of cholesterol (Zhou et al., 2021 ). SR‐B1 can change the distribution of cholesterol on the cell membranes, thereby mediating the uptake and reverse transport of cholesterol, and facilitating the efflux of cholesterol (Li, Sun, et al., 2020 ). The results of the current study revealed that IOP‐A could increase the expression of CYP7A1 and SR‐B1 proteins in the liver of diet‐induced hyperlipidemic rats.…”
Section: Discussionmentioning
confidence: 99%
“…When the activity of CYP7A1 decreases, the conversion of cholesterol to bile acid is blocked, resulting in an increased level of cholesterol (Zhou et al., 2021 ). SR‐B1 can change the distribution of cholesterol on the cell membranes, thereby mediating the uptake and reverse transport of cholesterol, and facilitating the efflux of cholesterol (Li, Sun, et al., 2020 ). The results of the current study revealed that IOP‐A could increase the expression of CYP7A1 and SR‐B1 proteins in the liver of diet‐induced hyperlipidemic rats.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the published study also proved that kaempferol and kaempferide decreased the expression levels of FAS and PPARγ (Tie et al, 2021). Unexpectedly, Al intervention did not significantly enhance the gene expression level of CPT1A, a rate‐limiting enzyme responsible for β‐oxidation of long‐chain fatty acids (Li et al, 2020). In addition, the data implied that fat‐5, fat‐6, fat‐7, sbp−1, cebp‐2, nhr‐49, nhr‐80 and mdt−15 might be important genes involved in reduced lipid accumulation in C. elegans by Al treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The cells were cultured in DMEM containing 10% FBS and 1% penicillin–streptomycin and incubated with 5% CO 2 at 37 °C. Cells were allowed to grow to approximately 80% confluency and were sub-cultured at a ratio of 1:3 [ 27 ]. In this study, to simulate the process of nonalcoholic fatty liver disease in vitro, 0.2 mM oleic acid (OA) was added to the culture medium for 48 h to induce human HepG2 to establish a nonalcoholic fatty liver cell model [ 28 ].…”
Section: Methodsmentioning
confidence: 99%